COMMUNITY PARTICIPATION FOR SUSTAINABLE INCLUSION OF EDUCATIONALLY DEPRIVED CHILDREN IN SCHOOLS OF NORTH DINAJPUR, WEST BENGAL, INDIA - Abhishek, Dey; Indranil, Sarkar (INTI International University, 2023)
The paper delves into the sustainability aspect of child education, emphasizing the widespread agreement on the crucial role of community involvement in improving the quality of education. This consensus is underpinned by the Right to Education (RTE) Act of 2009, which mandates the establishment of School Management Committees (SMCs) comprising parents, teachers, and local authorities. The primary objective of these committees is to enhance educational outcomes and create a conducive learning environment. Research consistently underscores the positive correlation between parental engagement and children's academic success. However, it is crucial to note that effective engagement in rural areas must be tailored to local contexts. The paper's focus on North Dinajpur district stems from the region's alarming literacy rates, particularly among females, with only 36.5%. Additionally, the high prevalence of early marriages, affecting 39% of the population, serves as a compelling motivation for this study. Drawing on prior experiences and available data, the present paper sets out to evaluate community-driven initiatives aimed at mainstreaming educationally disadvantaged children into elementary schools. Emphasis is placed on the imperative of a rights-based approach, highlighting that education is a fundamental right for all children, regardless of their background. The study meticulously examines whether social work interventions and community strengthening efforts contribute to the sustainable inclusion of marginalized children within the educational system. It also seeks to unravel the multifaceted dynamics in rural and urban North Dinajpur, shedding light on the challenges and successes of community-driven educational initiatives to mainstream out-of-school children in schools. Ultimately, the paper strives to contribute valuable insights into the broader discourse on education quality and community participation, with the aspiration of improving educational outcomes for all children, especially those facing socio-economic challenges in rural and urban areas.